Understanding Civilized Politics: Reconstruction of Pancasila Ideology and Political Ecology - Thomas Tokan Pureklolon; Jhon Maxwell Yosua Pattinusa (International Forum of Researchers and Lecturers, 2025)
This Study Aims To Understand The Concept Of Civilized Politics In The Context Of Pancasila Ideology And Political Ecology. Using A Philosophical Approach, This Study Analyzes How Pancasila Ideology Can Be A Foundation For Civilized And Sustainable Politics. This Study Also Discusses The Importance Of Political Ecology In Understanding The Relationship Between Humans And The Environment. The Method Used In This Study Is A Qualitative Method. This Article Uses A Critical Analysis Method To Discuss The Concept, Object, Method, And Benefits Of A Reconstruction Of Pancasila Ideology And Political Ecology Which Are Useful For Policy Makers Who Want To Understand How Pancasila Ideology Can Be Implemented In Civilized And Sustainable Politics And Are Useful For The General Public Who Want To Understand About Civilized And Sustainable Politics In The Context Of Indonesia. Critical Analysis Is A Systematic And Objective Method For Analyzing And Evaluating Information (Fairclough, 1995, P. 20). By Using The Critical Analysis Method, This Article Can Find The Strengths And Weaknesses Of Sociolinguistics In Education In Improving The Quality Of Learning. The Results Of The Research Or What Is To Be Achieved In This Research Is That The Pancasila Ideology Can Be The Basis For Civilized And Sustainable Politics If Implemented By Paying Attention To The Principles Of Political Ecology. This Research Contributes To The Understanding Of Civilized And Sustainable Politics In The Indonesian Context.